Reciprocal proteasome-mediated degradation of PIFs and HFR1 underlies photomorphogenic development in Arabidopsis - Xu, Xiaosa (Development, 2017)
The phytochrome-mediated regulation of photomorphogenesis under red and far-red light conditions involves both positively and negatively acting factors. The positively acting factors (e.g. HY5/HFR1/LAF1 and others) are degraded in the dark to prevent photomorphogenesis. By contrast, the negatively acting factors (e.g. phytochrome-interacting factors or PIFs) are degraded in response to light to promote photomorphogenesis. Here, we show that the negatively acting factor PIF1 is also degraded in the dark by direct heterodimerization with the positively acting factor HFR1. Conversely, PIF1 also promotes the degradation of HFR1 in darkness. PIF1 enhances the poly-ubiquitylation of HFR1 by COP1 in vivo and in vitro. In addition, the reciprocal co-degradation of PIF1 and HFR1 is dependent on the 26S proteasome pathway in vivo. Genetic evidence shows that the hfr1 mutant partially suppresses the constitutive photomorphogenic phenotypes of cop1-6 pif1 and of the quadruple mutant pifq both in the dark and in far-red light conditions. Taken together, these data uncover a co-degradation mechanism between PIFs and HFR1 that underlies photomorphogenic development in Arabidopsis thaliana.